HAEMATOLOGICAL AND BIOCHEMICAL INDICES OF BROILERS FED DIET WITH Moringa oleifera LEAF MEAL (MOLM) - L. Murali; K. Naga Raja Kumari; D. Narendra Nath; D. Srinivas Kumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was carried out to study the effect of dietary inclusion of Moringa oleifera leaf meal (MOLM) on blood and serum parameters of broilers. Day old broilers (n=180) were distributed randomly into six dietary groups each with five replicates of 6 birds. The dietary treatments include Moringa oleifera leaf meal at 0% (T1; negative control), T1 + Vit-E, Se, Vit-C (T2; positive control), 1.5% (T3), 3.0% (T4), 4.5% (T5) and 6.0% (T6) levels by marginal adjustment of other feed ingredients. PCV, Hb, RBC, WBC and H/L ratio were not inÀuenced by the level of MOLM in diet. Decreased (p<0.01) serum cholesterol and increased HI titers (p<0.05), serum protein (p<0.05), globulin (p<0.01) with increasing MOLM in diets. Results showed that MOLM can be included up to 6% without any deleterious effect on health status of the broilers and meat production with low cholesterol.